A controlled study comparing visual function in patients treated with vigabatrin and tiagabine. Issue 3 (1st March 2003) - Krauss, G L; Johnson, M A; Sheth, S; Miller, N R
Abstract : Objective: Vigabatrin treatment is frequently associated with irreversible retinal injury and produces retinal electrophysiological changes in nearly all patients. Concern has been raised that tiagabine and other antiepilepsy drugs (AEDs) that increase brain γ-aminobutyric acid (GABA) might produce similar electrophysiological and clinical changes in visual function. The study compared visual function between groups of patients with epilepsy treated long term with tiagabine, vigabatrin, and patients treated with other AEDs. Methods: A cross sectional study comparing visual acuity, colour vision, static and kinetic perimetry, and electroretinograms between groups of patients treated with tiagabine, vigabatrin, and other AEDs (control patients). Patients were adults receiving stable AED treatment for >6 months. Results: Vigabatrin treated patients had marked visual field constrictions in kinetic perimetry (mean radius 39.6° OD, 40.5° OS), while tiagabine patients had normal findings (mean 61° OD, 62° OS) (differences OD and OS, p=0.001), which were similar to epilepsy control patients (mean 60° OD, 61° OS). Vigabatrin patients had abnormal electroretinographic photopic B wave, oscillatory, and flicker responses, which correlated with visual field constrictions. These electroretinographic responses were normal for tiagabine patients and control patients. Patients were treated with vigabatrin for a median of 46 months compared with 29 months for tiagabine. Patients taking other AEDs that may change brain GABA had normal visual function. Conclusion: Unlike vigabatrin, tiagabine treatment is associated with normal electroretinography and visual fields and ophthalmological function similar to epilepsy control patients. Differences between vigabatrin and other GABA modulating AEDs in retinal drug concentrations and other effects might explain why tiagabine increases in GABA reuptake do not cause retinal injury.